High Performance Thin Layer Chromatography method for analysis of 3,4-methylenedioxymethamphetamine in seized tablets - Boris E. Duffau; Sonia Rojas; Lorena A. Delgado; Sebastián Jofré (GarVal Editorial Ltda., 2015)
Context: Consumption of synthetic drugs had increased in recent years, used as a recreational drug by young people who presume that consumption of this drug is harmless for health; however clinical studies have shown that this stimulant and its metabolites are toxic. Due to these reasons, chemical analysis of this illicit drug is crucial from the points of view of occupational medicine, toxicology, and law enforcement with the aim of pursuit the traffic of illegal drug. Aims: Implement and fully validate a rapid and simple method for detection and quantitation of MDMA by High-Performance Thin Layer Chromatography in seized samples. Methods: With the implemented method was analyzed 12 positive samples seized by Chilean police, to found the concentration of MDMA in ecstasy tablets. Results: The method was fully validated, the linearity of the method was evaluated by the calibration curve between 51.0 - 510.0 µg/band (R2 0.9977); limit of detection was 12.1 µg per band, and limit of quantitation was 36.8 µg per band. The precision of the method (RSD) was lower than 5.0%. Accuracy was evaluated by determination of the percentage of MDMA recovered by the assay (99.13%), and relative Uncertainty was 6.66%. With this method, it was analyzed real seized samples of MDMA, results showed that all samples contained MDMA and concentration was between 18.15 - 59.84 % w/w. Conclusions: The method is selective, sensitive, and specific, with possible application in forensic analysis. To the best of our knowledge, this is the first report about concentration of MDMA in ecstasy pills in Chile.